PENGARUH INFORMASI AKUNTANSI (ROA, LEVERAGE, SALES GROWTH, CAPITAL INTENSITY DAN COMPANY SIZE) DAN COMPANY AGE TERHADAP TAX AVOIDANCE - Pri Anggun Novria Fajarwati; Wita Ramadhanti (Universitas Wiralodra, 2021)
This study aims to analyze the influence of financial information (profitability, leverage, sales growth, capital intensity and company size) and company age on tax avoidance. The dependent variable used in this study is tax avoidance which is proxied by the effective tax rate (ETR), while the independent variables are company size, company age, profitability (ROA), leverage (DAR), sales growth, and capital intensity. The population in this study are mining companies listed on the Indonesia Stock Exchange (BEI) for the period 2012-2016. The sample in this study used a purposive sampling method and obtained 55 samples of observations. Data analysis was performed using analysis tools Partial Least Square (PLS). The results of the analysis show that leverage has a positive effect on tax avoidance. Meanwhile, profitability, company size, company age, sales growth, and capital intensity have no effect on tax avoidance.